2019
DOI: 10.1111/1471-0528.15970
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth phenotypes in women with autoimmune rheumatic diseases: a population‐based cohort study

Abstract: Objective To investigate preterm birth (PTB) phenotypes in women with different autoimmune rheumatic diseases in a large population‐based cohort. Design Retrospective cohort study. Setting California, USA. Population All live singleton births in California between 2007 and 2011 were analysed. Patients with autoimmune disease at delivery were identified by International Classification of Diseases, Ninth Revision , Clinical Modification (ICD‐9‐CM), codes for systemic lupus erythematosus (SLE), systemic sclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 46 publications
(86 reference statements)
7
23
0
Order By: Relevance
“…We identified women with IIM from both inpatient and outpatient clinics, and therefore disease activity may have varied from mild to severe, which might explain the difference between our findings and the Australian study although our study did not find any different risk estimates among births to women with IIM identified from the inpatient vs the outpatient register. Besides, Kolstad et al recently found that the risk of early preterm birth (7.9% vs 1.0%, aRR = 10.0; 95% CI: 3.2, 31.1) was particularly high in 38 births of women with DM/PM compared with controls [ 9 ], which is in line with our findings. Two previous studies including women with IIM prior to pregnancy also observed lower mean birth weight among cases with active IIM compared with cases with inactive IIM [ 4 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…We identified women with IIM from both inpatient and outpatient clinics, and therefore disease activity may have varied from mild to severe, which might explain the difference between our findings and the Australian study although our study did not find any different risk estimates among births to women with IIM identified from the inpatient vs the outpatient register. Besides, Kolstad et al recently found that the risk of early preterm birth (7.9% vs 1.0%, aRR = 10.0; 95% CI: 3.2, 31.1) was particularly high in 38 births of women with DM/PM compared with controls [ 9 ], which is in line with our findings. Two previous studies including women with IIM prior to pregnancy also observed lower mean birth weight among cases with active IIM compared with cases with inactive IIM [ 4 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Prior studies on other inflammatory diseases such as rheumatoid arthritis and systemic lupus erythematosus have shown that the disease influences rates of preterm birth and pregnancy loss. 2 No statistically significant differences were detected when comparing our study cohort with the general population of women in the US in terms of the rates of miscarriage, 3 C-section, 4 premature baby, 4 stillbirth 5 and perinatal mortality. 5 In addition, baseline HS disease severity was not significantly associated with poorer pregnancy or neonatal outcomes.…”
Section: Referencesmentioning
confidence: 66%
“…1 The National Institute for Health and Care Excellence recommends specialist review if cellulitis has not improved after 14 days despite antibiotics. 2 The 2017 Cellulitis Priority Setting Partnership prioritized research into diagnosis and treatment of cellulitis. 3 Cellulitis diagnosis is based on history, examination and inflammatory markers.…”
mentioning
confidence: 99%
“…42 The extent and timing of this cytokine cascade inevitably requires precise control, as excess inflammation (ie generated by autoimmune disease) may instigate early-onset delivery as epitomized in preterm labour. 33,43,44…”
Section: Infl Ammati On In Impl Antati On and Parturitionmentioning
confidence: 99%